ANALISIS FAKTOR RESIKO KEBERADAAN JENTIK NYAMUK Aedes aegypti DI KELURAHAN TUAH KARYA WILAYAH PUSKESMAS SIDOMULYO - Rulen, Betty Nia; Fitria, Eliza; Seprina, Zurni; Rahayu, Rahayu; Fentia, Lia (Ensiklopedia of Journal, 2024)
Dengue hemorrhagic fever (DHF) is a viral disease transmitted by mosquitoes that has spread rapidly in all regions of the world in recent years. Currently, dengue fever is still a health problem in both urban and semi-urban areas. Vector behavior and its relationship with the environment, such as climate, vector control, urbanization, etc. influence the occurrence of dengue fever outbreaks in urban areas. The aim of this research is to determine the risk factors associated with the presence of Aedes Aegypti mosquito larvae in Tuah Karya Village, Sidomulyo Health Center Area. This research design uses a cross sectional approach with the Chi-square test. Data collection methods are carried out through measurements, interviews, questionnaires and observation. The population of all heads of families (KK) in the Tuah Karya Subdistrict, Tuah Madani District is 7,624 families using cluster sampling as a sampling technique with a sample size of 100 respondents. The research results showed a significant relationship between pH (p value = 0.000), water turbidity (p value= 0.000), the presence of a landfill (p value = 0.000), level of knowledge (p value = 0.000) and the presence of mosquito larvae, while there was no significant relationship. significant relationship between PSN behavior and the presence of mosquito larvae (p value = 0.137). It is hoped that the Sidomulyo Community Health Center will routinely monitor the landfill by checking community bathtubs, routinely distributing abate powder, routinely conducting fogging, larva surveys and conducting outreach to increase community knowledge. Keywords : Aedes aegypti, pH, Landfill presence, Knowledge, PSN, Mosquito Larvae